The Level Of The Use Of Zone Of Proximal Development Practices For The Diploma Students. Field Study At Faculty Of Education At Tishreen University - Hamdan, Maisaa (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This Study Aimed To Identify The Level Of Tthe Use Of Zone Of Proximal Development Practices For The Diploma Students At Faculty Of Education At Tishreen University. The Descriptive Approach Was Used. The Research Sample Was Comprised Of (81) Students From Diploma Students At Faculty Of Education At Tishreen University They Were Purposely Chosen. To Achieve The Objectives Of The Research, Questionnaire Tool Designed By The Researcher Was Used Which Consisted Of (33) Item Is Sub-Divided Into (6) Domains Represent Instructional Zone Of Proximal Development Practices Stages. The Validity And Reliability Tool Had Been Verified And Established, The Results Revealed That The Diploma Students Practice The Zone Of Proximal Development As a Whole And All Skill Alone. Results Also Showed That The Viewpoints Of the Learners Were Similar In Assessment The Level Of Practice Of Zone Of Proximal Development There Were No Statistically Significant Differences At The Mean Scores (α≤ 0.05) Attributed To The Variables: Academic Qualification, Years Of Experience And Six Variable.